Ge Incorporation to Stabilize Efficient Inorganic CsPbI3 Perovskite Solar Cells. Issue 10 (27th January 2022) - Meng, Fanqi; Yu, Bingcheng; Zhang, Qinghua; Cui, Yuqi; Tan, Shan; Shi, Jiangjian; Gu, Lin; Li, Dongmei; Meng, Qingbo; Nan, Cewen
Abstract: Aiming at stable CsPbI3 perovskite solar cells, Ge incorporated for the first time into DMAPbI3 ‐based precursor systems. Ge incorporation is found to be able to modify crystallization growth of CsPb1− x Ge x I3 films and reduce annealing temperature and treatment time by lowering CsPbI3 formation energy. The champion power conversion efficiency (PCE) of 19.52% is achieved with a certified PCE of 18.8%, which is the highest performance of CsPbI3 PSCs with alien element‐doping. In addition, in situ formation of GeO2 can passivate the grain boundary and surface defects, thus significantly improving the moisture resistance of the perovskite film and related devices. Excellent operational stability is achieved with no PCE degradation over 3000 h at a fixed bias voltage of 0.85 V under continuous white LED (6500 K) illumination and a nitrogen atmosphere. This work demonstrates that Ge‐incorporation is a promising way to stabilize CsPbI3 perovskite solar cells by simultaneously improving perovskite crystallinity and passivating the grain boundary and interfacial defects. Abstract : Ge is incorporated for the first time into CsPbI3 ‐based perovskites. Ge incorporation can modify crystallization growth of CsPb1− x Ge x I3 films and passivate grain boundary and interfacial defects. The CsPb0.95 Ge0.05 I3 ‐based perovskite solar cell (PSC) presents 19.52% efficiency with a certified efficiency of 18.8%. In addition, moisture resistance properties and excellent operational stability are also achieved.